Weight estimation on static B-WIM algorithms: A comparative study. (1st November 2019) - Carraro, Felipe; Gonçalves, Matheus Silva; Lopez, Rafael Holdorf; Miguel, Leandro Fleck Fadel; Valente, Amir Mattar
Highlights: Different methods were theoretically analyzed by their statistical background. These methods were evaluated experimentally using real-world data signals. The evaluated methods performed similarly for both considered bridges. Trends in methods comparison were observed as a function of the model suitability. Abstract: Bridge weigh in motion (B-WIM) comprises the use of sensors on existing bridges in order to assess the loads of passing vehicles. Although numerous methods for weight estimation on static B-WIM algorithms may be found in the literature, there is not available a comparison study among them, especially regarding accuracy and statistical assumptions. Hence, this paper provides a critical comparison on a subset of conceptually similar B-WIM methods, further extending the discussion on their theoretical assumptions, beyond what is currently available in literature. The methods are not only referenced but reinterpreted and reformulated in a unifying manner, allowing an in-depth comparison. Moreover, a parametric study on the performance and sensitivity of methods is conducted. Not only simulated but also real data are employed in the comparison, supporting conclusions.